2016
DOI: 10.11591/aptikom.j.csit.94
|View full text |Cite
|
Sign up to set email alerts
|

Survey Based Classification of Bug Triage Approaches

Abstract: This paper presents a comprehensive survey of bug triaging approaches in three classes namely machine learning based, meta-data based and profile based. All approaches under three categories are critically compared and some potential future directions and challenges are reported. Findings from the survey show that there is a lot of scope to work in cold-start problem, developer- profiling, load balancing, and reopened bug analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the coverage of these articles is not comprehensive, and they do not specifically focus on runtime information for classifica-tion. Yadav et al surveyed classification methods based on machine learning, profiles, or metadata, comparing and discussing the pros and cons of different approaches [16]. They concluded that no single method has advantages in all dimensions and provided insights into potential research points such as the cold activation problem and load balancing.…”
Section: Related Surveymentioning
confidence: 99%
“…However, the coverage of these articles is not comprehensive, and they do not specifically focus on runtime information for classifica-tion. Yadav et al surveyed classification methods based on machine learning, profiles, or metadata, comparing and discussing the pros and cons of different approaches [16]. They concluded that no single method has advantages in all dimensions and provided insights into potential research points such as the cold activation problem and load balancing.…”
Section: Related Surveymentioning
confidence: 99%